HISTOPATHOLOGICAL CHANGES LIVER IN KAMPUNG CHICKEN GIVEN HERBAL MEDICINE OF ASHITABA AND AVIAN INFLUENZA VACCINE - Pratama, I Gede Made Andy; Sudira, I Wayan; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana; Vol. 14 No. 5 October 2022DO - 10.24843/bulvet.2022.v14.i05.p11, 2022)
Ashitaba plant ( Angelica keiskei ) is one of the original herbal plants from Japan which physically resembles celery leaves and can treat various diseases. This study aims to see the effect of giving ashitaba leaf herbal medicine on the histopathological picture of native chicken liver ( Gallus domesticus ) as seen from the proliferation of Kupffer cells in sinusoids vaccinated with Avian influenza (AI) vaccine. This study used a completely randomized design and used 25 native chickens. The study consisted of a treatment group, namely giving Ashitaba leaf herbal medicine (control), as well as giving Ashitaba leaf herbal medicine with doses of 50, 100, 200, and 400 mg / head / day respectively for 14 days by mixing it in drinking water until the volume was 100 ml. On the 21st day, all groups of chickens were vaccinated with the Avian Influenza vaccine. Liver from samples taken on day 42, to be made preparations and stained with Hematoxylin-Eosin staining. Sample under a microscope at 400x magnification. The variable observed was the proliferation of kupffer cells in the sinusoids with the histopathological change scoring scale. The research data were analyzed non-parametrically using the Kruskal-Wallis test. The results showed that giving the herb Ashitaba leaves with a dose range of 50 mg / head / day to 400 mg / head / day for 14 days, did not cause significant changes in the histopathology of native chickens when seen from the proliferation of Kupffer cells in the sinusoids that had been induced by avian influenza vaccine.